Bioremediation potential of Bacillus sp. and Paenebacillus sp. novel lead-resistant isolates: Identification, characterization, and optimization studies - Harun, Fatima Abdullahi; Yakasai, Hafeez Muhammad; Jagaba, Ahmad Hussaini; Usman, Shehu; Umar, Hassan Abba; Shukor, Mohd Yunus (Elsevier, 2024)
Environmental pollution by heavy metals and other toxic substances has increasingly become a global health concern. Lead is a hazardous environmental contaminant that is been released to the surface causing deleterious health effects to man. Various strategies have been employed such as excavation, precipitation, and vitrification to remove lead from polluted sites. However, bioremediation of heavy metal contaminated sites has served as a cost-effective and ecofriendly tool for detoxifying and restoration of ecological entities. In this study, we reported the isolation and optimization of two novel lead-resistant isolates from active goldmine contaminated site of Anka, Zamfara state Nigeria. Results of Atomic Absorption Spectroscopy (AAS) showed higher lead concentration from the sampled sites (p<0.05) than the USEPA standard (400 mg/Kg). Paenebacillus sp. strain BUK_BCH_BTE 3 (MT160418) and Bacillus sp. strain BUK_BCH_BTE 4 (MT160452) were identified based on the 16 S rRNA partial gene sequencing of the locally isolated microorganisms. Characterization of the two isolates revealed optimum growth at 37 °C, a pH of 7.0 over 48 hrs while utilizing inoculum volumes of 100 µL each. The two isolates utilized optimum sucrose concentrations at 10–20 g/L, while 5 g/L nitrogen source and 5 g/L of urea were optimum for Paenebacillus sp. as well as Bacillus sp. respectively. An optimal lead concentration of 1000 g/L was obtained by both isolates. Furthermore, the two isolates tolerated up to 3000 mg/L lead nitrate. Mercury, a toxic heavy metal, was noticed to hinder the growth of both isolates significantly at p<0.05. Hence, the locally isolated Paenebacillus sp. and Bacillus sp. could be used as promising tools for bioremediation of lead-contaminated environment.